Indescribable - Giglio, Louie; Sparrow Records (Brentwood, TN : Distributed by Sparrow Records, 2009)
Louis Giglio delivers a talk about God's creation of the universe, with images of space photography.
DVD; Dolby digital.
Title and credits from container.
Louis Giglio.
Closed-captioned
Keywords: God (Christianity); Praise of God; Space photography; Video recordings for the hearing imparied; DVD-Video discs